KOMPETENSI PERADILAN UMUM DAN PERADILAN TATA USAHA NEGARA DALAM PEMBATALAN RISALAH LELANG (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 205 PK/ Pdt/ 2010) - , Saurma Tambunan, Dwi Haryati S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
PUPN execution auction is an effort made by the government in order to erect law on debtor who does not fulfill specified agreement (wanprestasi). Implemented auction is included in an official report generally called action treatise which, according to Financial Ministerâs Rule Number 93/PMK.06/2010 on Instruction of Action Implementation, cannot be annulled by existing rule, so, in Book II, the Supreme Court states that action can be annulled by claim to the Court. So that it is attractive to study judicature power which will examine, decide and solve claim of the action treatise annulment. This research is a juridical-normative study supported by juridicalempirical study, conducted by study of literature and field study with guided interview. Data were analyzed by deductive method, this research was expected to give responsible conclusions. Based on this research, it is indicated that auction treatise report annulment became unclear phenomenon because application for annulment was submitted to general judicature and PTUN, whereas powers of both judicatures are different. Different considerations of judges in interpreting existing rules resulted in different verdicts so that it does not reflect legal certainties. Interpretation that auction treatise annulment is power of PTUN because it is product of TUN Official, auction official. Auction treatise as case object of PTUN does not meet requirement as perfect case object of TUN because legal action of the auction treatise is civil law action which is exception as case of TUN mentioned in Article 2, Letter a, of UUPTUN. Auction treatise as an official report of auction implementation is case object of civil law because it is ownership case with factor of action without compliant with law in implementing the auction containing civil action elements, so that it is not power of PTUN but it is power of public judicature (PN).